Modulation of host adaptive immunity by hRSV proteins - Espinoza, Janyra A (Landes Bioscience, 2014)
Globally, the human respiratory syncytial virus (hRSV) is the major cause of lower respiratory tract infections (LRTIs) in infants and children younger than 2 years old. Furthermore, the number of hospitalizations due to LRTIs has shown a sustained increase every year due to the lack of effective vaccines against hRSV. Thus, this virus remains as a major public health and economic burden worldwide. The lung pathology developed in hRSV-infected humans is characterized by an exacerbated inflammatory and Th2 immune response. In order to rationally design new vaccines and therapies against this virus, several studies have focused in elucidating the interactions between hRSV virulence factors and the host immune system. Here, we discuss the main features of hRSV biology, the processes involved in virus recognition by the immune system and the most relevant mechanisms used by this pathogen to avoid the antiviral host response.